Collections and decorations: an original approach to the dissemination of prehistoric collections in Germany in the nineteenth century - Lichter, Clemens (Journal of the history of collections, 2017)
The article examines how antiquities were dealt with at the end of the nineteenth century. Thirteen assemblages of prehistoric stone tools from Denmark - similar in size, composition, arrangement as well as in their historical migration to public institutions - can be identified in several museum collections (e.g. Braunschweig, Bucharest, Darmstadt, Karlsruhe, Meiningen, Munich, Stuttgart). Seven different donors are identified as the originators of the thirteen collections investigated. Their motivation is examined against the setting of the end of the nineteenth century, leading to the identification of further, similarly motivated donations made at that time. The supply of antiquarian specimens, on the one hand fulfilling the demand from museums and on the other answering the appetite of the donors for the honours and decorations awarded by aristocratic courts, brought about a marked increase in collections of antiquities.